1969
DOI: 10.1021/ed046p799
|View full text |Cite
|
Sign up to set email alerts
|

Computing ligand field potentials and relative energies of d orbitals: A simple general approach

Abstract: This approach to ligand field theory permits the derivation of the expressions for ligand field potentials and the quantitative evaluation of the energies of d orbitals in a large variety of geometrical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 7 publications
(14 reference statements)
5
53
0
Order By: Relevance
“…The cis ‐N–Fe–N bond angles are evidence for a distorted octahedral arrangement, but the magnitude of the prismatic distortion expressed by the value Σ is smaller than the similar non‐methylated compound 4 (Table 3). 14 The distance from the methyl carbon to the nearest nitrogen of the adjacent pyridine ring is similar to the value found in the structure of 8 in LS state; it is equal to ca. 3.030 Å.…”
Section: Crystal Structures Of 1–5supporting
confidence: 77%
See 1 more Smart Citation
“…The cis ‐N–Fe–N bond angles are evidence for a distorted octahedral arrangement, but the magnitude of the prismatic distortion expressed by the value Σ is smaller than the similar non‐methylated compound 4 (Table 3). 14 The distance from the methyl carbon to the nearest nitrogen of the adjacent pyridine ring is similar to the value found in the structure of 8 in LS state; it is equal to ca. 3.030 Å.…”
Section: Crystal Structures Of 1–5supporting
confidence: 77%
“…According to Gillum et al,13 pronounced M d –L π * ‐back‐bonding (confirmed by IR and UV/Vis spectroscopy, vide infra) can decrease the bond order of the C=N group by decreasing the rotational barrier of the bond, which explains the observed deviation. This is caused by the strong tendency of LS Fe II to form an energetically favorable pseudo‐octahedral arrangement of donor atoms,14 but this competes with the rigidity of the ligand, which prefers trigonal prismatic conformation.…”
Section: Crystal Structures Of 1–5mentioning
confidence: 99%
“…Previously, we argued that this trend was a consequence of increased crystal field stabilization that would be achieved by flattening to a D 2 d structure. 34 Interestingly, the trend reverses at Co (τ 4 = 0.59), which features a d 5 electronic configuration. Presumably, once a d 5 configuration is achieved, at least one d electron must occupy an anti-bonding or partially anti-bonding orbital, which results in a decrease of the crystal field stabilization.…”
Section: Resultsmentioning
confidence: 95%
“…This is still lacking in conventional ligand field theory, despite valiant attempts [13,14]. The simplicity can be illustrated with the example of a trans-CrA 4 B 2 complex.…”
Section: In the Beginningmentioning
confidence: 99%